2021
DOI: 10.2478/ausae-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the influence of maize (Zea mays) and cowpea (Vigna unguiculata L. Walp) growth period on some thermal and hydrological properties of two soils with textural class variation

Abstract: Adequate knowledge of soil processes is key to ensuring sustainability. Towards a better understanding of some thermal and hydrological processes that take place in the soil as a result of the growth period of maize and cowpea, a concurrent research was carried out in two different locations with soil textural variation (sandy clay loam and clay loam) at the Federal University of Technology, Akure. The treatment consisted of bare soil plot, cowpea plot, and maize plot arranged in a randomized complete block de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Major et al (2012c) reported that the amendment of soil low in fertility with wood biochar at 20 t/ha increased the concentration of nitrate (NO -N) in the soil 3 solution. Akingbola et al (2021; reported that the ability of biochar to retain soil nutrients and improve the water-holding capacity of soil may have direct effects on increasing crop yield and water use efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major et al (2012c) reported that the amendment of soil low in fertility with wood biochar at 20 t/ha increased the concentration of nitrate (NO -N) in the soil 3 solution. Akingbola et al (2021; reported that the ability of biochar to retain soil nutrients and improve the water-holding capacity of soil may have direct effects on increasing crop yield and water use efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar is highly recalcitrant due to its condensed structure (Spokas et al, 2012) and is derived from the thermal decomposition of biomass in an environment with low or no oxygen at moderately low temperatures. Several studies have shown that biochar can ameliorate soil nutrients status, cation exchange capacity in the soil, soil structure, nutrient use efficiency, waterholding, nutrient-holding capacity, and saturated hydraulic conductivity, while decreasing soil acidity (Lehmann et al, 2006;Asai et al, 2009;Karhu et al, 2011;Akingbola et al, 2021Akingbola et al, , 2022. Increases in yield with biochar application have been reported for crops such as cowpea (Yamato et al, 2006), soybean (Tagoe et al, 2008), maize (Yamato et al, 2006;Rodríguez et al, 2009), upland rice (Asai et al, 2009), paddy rice (Shackley et al, 2011;Sokchea and Preston, 2011) and water spinach (Southavong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%